What does π \pi have to do with ln \ln integrals ?

Calculus Level 5

0 1 ln x ( ln ( 1 x ) ) 2 x d x = a π b c , \int_0^1 \frac{\ln x \left(\ln(1-x)\right)^2}{x} dx = \frac{-a \pi^b}{c},

where a , b , c a,b,c are positive integers and gcd ( a , c ) = 1. \gcd(a,c)=1. Find a + b + c . a+b+c.


The answer is 185.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Tunk-Fey Ariawan
Aug 6, 2014

Before we evaluate the integral, let us first notice the following propositions which would help us to evaluate the given integral.

Proposition 1 : n = 1 H n x n = ln ( 1 x ) 1 x ; for x < 1 , \sum_{n=1}^\infty H_n x^n=-\frac{\ln(1-x)}{1-x}\quad;\quad\text{for}\ |x|<1, where H n H_n is the n n -th harmonic number .

Proof :

Since H n H n 1 = 1 n H_n-H_{n-1}=\frac{1}{n} for n Z + n\in\mathbb{Z}_+ , then multiplying both sides by x n x^n yields H n x n H n 1 x n = x n n n = 1 H n x n n = 1 H n 1 x n = n = 1 x n n n = 1 H n x n x n = 1 H n 1 x n 1 = ln ( 1 x ) ( 1 x ) n = 1 H n x n = ln ( 1 x ) Q.E.D. \begin{aligned} H_n x^n-H_{n-1}x^n&=\frac{x^n}{n}\\ \sum_{n=1}^\infty H_n x^n-\sum_{n=1}^\infty H_{n-1}x^n&=\sum_{n=1}^\infty\frac{x^n}{n}\\ \sum_{n=1}^\infty H_n x^n-x\sum_{n=1}^\infty H_{n-1}x^{n-1}&=-\ln(1-x)\\ (1-x)\sum_{n=1}^\infty H_n x^n&=-\ln(1-x)\qquad\text{Q.E.D.} \end{aligned} where H 0 = 0 H_0=0 , and H 1 = 1 H_1=1 .


Proposition 2 : n = 1 H n n 3 = π 4 72 . \sum_{n=1}^\infty\frac{H_n}{n^3}=\frac{\pi^4}{72}. Proof :

We have H n = m = 1 ( 1 m 1 m + n ) = m = 1 n m ( m + n ) . H_n=\sum_{m=1}^\infty\left(\frac{1}{m}-\frac{1}{m+n}\right)= \sum_{m=1}^\infty \frac{n}{m(m+n)}. Therefore n = 1 H n n 3 = m , n 1 1 n 2 m ( m + n ) = m , n 1 1 m 2 n ( n + m ) . \sum_{n=1}^\infty\frac{H_n}{n^3}=\sum_{m,n\geq1}\frac{1}{n^2m(m+n)} =\sum_{m,n\geq1}\frac{1}{m^2n(n+m)}. Taking the half sum we obtain n = 1 H n n 3 = 1 2 m , n 1 1 m n ( m + n ) ( 1 m + 1 n ) = 1 2 m , n 1 1 m 2 n 2 = 1 2 ζ 2 ( 2 ) = 1 2 ( π 2 6 ) 2 Q.E.D. \begin{aligned} \sum_{n=1}^\infty\frac{H_n}{n^3}&=\frac{1}{2}\sum_{m,n\geq1}\frac{1}{mn(m+n)}\left(\frac{1}{m}+\frac{1}{n}\right)\\ &=\frac{1}{2}\sum_{m,n\geq1}\frac{1}{m^2n^2}\\ &=\frac{1}{2}\zeta^2(2)\\ &=\frac{1}{2}\left(\frac{\pi^2}{6}\right)^2\qquad\qquad\qquad\text{Q.E.D.} \end{aligned}

Proposition 3 : 0 1 x α ln n x d x = ( 1 ) n n ! ( α + 1 ) n + 1 , for n = 0 , 1 , 2 , \int_0^1 x^\alpha \ln^n x\ dx=\frac{(-1)^n n!}{(\alpha+1)^{n+1}}, \qquad\text{for }\ n=0,1,2,\ldots

Proof :

Note that 0 1 x α d x = 1 α + 1 , for α > 1. \int_0^1 x^\alpha\ dx=\frac1{\alpha+1},\qquad\text{for }\ \alpha>-1. Differentiating n n times yields 0 1 n α n ( x α ) d x = 0 1 x α ln n x d x = ( 1 ) n n ! ( α + 1 ) n + 1 , for n = 0 , 1 , 2 , Q.E.D. \int_0^1 \frac{\partial^n}{\partial\alpha^n}\left(x^\alpha\right)\ dx=\int_0^1 x^\alpha \ln^n x\ dx=\frac{(-1)^n n!}{(\alpha+1)^{n+1}}, \qquad\text{for }\ n=0,1,2,\ldots\qquad\text{Q.E.D.}


Now, we will evaluate the given integral. Using the property a b f ( x ) d x = a b f ( a + b x ) d x \int_a^b f(x)\ dx=\int_a^b f(a+b-x)\ dx and also the previous propositions, then the given integral turns out to be 0 1 ln x ln 2 ( 1 x ) x d x = 0 1 ln ( 1 x ) ln 2 x 1 x d x = 0 1 n = 1 H n x n ln 2 x d x = n = 1 H n 0 1 x n ln 2 x d x = 2 n = 1 H n ( n + 1 ) 3 = 2 n = 1 1 ( n + 1 ) 3 ( H n + 1 1 n + 1 ) = 2 [ n = 1 1 ( n + 1 ) 4 n = 1 H n + 1 ( n + 1 ) 3 ] = 2 [ n = 1 1 n 4 n = 1 H n n 3 ] = 2 [ ζ ( 4 ) π 4 72 ] = 2 [ π 4 90 π 4 72 ] = π 4 180 . \begin{aligned} \int_0^1\frac{\ln x\ln^2(1-x)}{x}\ dx&=\int_0^1\frac{\ln(1-x)\ln^2 x}{1-x}\ dx\\ &=-\int_0^1\sum_{n=1}^\infty H_n x^n\ln^2 x\ dx\\ &=-\sum_{n=1}^\infty H_n\int_0^1 x^n\ln^2 x\ dx\\ &=-2\sum_{n=1}^\infty\frac{H_n}{(n+1)^3}\\ &=-2\sum_{n=1}^\infty\frac{1}{(n+1)^3}\left(H_{n+1}-\frac{1}{n+1}\right)\\ &=2\left[\sum_{n=1}^\infty\frac{1}{(n+1)^4}-\sum_{n=1}^\infty\frac{H_{n+1}}{(n+1)^3}\right]\\ &=2\left[\sum_{n=1}^\infty\frac{1}{n^4}-\sum_{n=1}^\infty\frac{H_{n}}{n^3}\right]\\ &=2\left[\zeta(4)-\frac{\pi^4}{72}\right]\\ &=2\left[\frac{\pi^4}{90}-\frac{\pi^4}{72}\right]\\ &=\large\color{#3D99F6}{-\frac{\pi^4}{180}}. \end{aligned} Thus, a + b + c = 1 + 4 + 180 = 185 \large a+b+c=1+4+180=\boxed{\color{#3D99F6}{185}} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...